Raven tales. Bald eagle [videorecording (DVD)] (Indigenous Collection., 2017)
In this episode, Eagle (Ian Reid) tells the children a story of the creation time when he and Raven (Dr. Evan Adams, Smoke Signals) are still young and the world is new. One day, the Great Spirit comes to visit and asks the brothers to fly him over the world he has created. According to Eagle, the Great Spirit rewards his service with a crown of white feathers on his head, but Raven remembers a different story and tells the children what really happened...